Properties of dense-graded asphalt mixture compacted at different temperatures. (January 2019) - Ismail, Sharudin; Abdul Hassan, Norhidayah; Yaacob, Haryati; Rosli Hainin, Mohd; Ros Ismail, Che; Mohamed, Azman; Khairul Idham Mohd Satar, Mohd
Abstract: Poor compaction work is one of the identified causes of road failure and has always been a concern to the asphalt industry. The use of compaction machinery, compaction temperature, weather factor and the type of mixture used could potentially affect the asphalt pavement performance. This study measures the properties of hot mix asphalt (dense-graded AC10) prepared at different compaction temperatures. Various compaction temperatures were selected for the laboratory slab samples preparation i.e. 152°C, 142°C, 132°C and 122°C. A 60/70 pen bitumen was used to prepare the slab with the size of 305mm x 305mm x 50mm. Thermocouple was used to monitor the temperature of the mix. The slab samples were then cored for cylindrical samples at the approximate size of 100mm diameter for mechanical tests. The core samples were tested for volumetric properties, degree of compaction (DOC), Marshall stability and resilient modulus. It was found that low compaction temperature increases the air void in the total mix (VTM) and decreases the air void filled with bitumen (VFB) due to the increase in bitumen viscosity. In other words, reduction in compaction temperature resists the compactibility of the loose mix and resulted in low final DOC and low modulus.